1936
DOI: 10.1097/00000658-193601000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cholecystitis Associated With Pancreatic Reflux

Abstract: IN I901, Opie'4 reported a case of acute hemorrhagic pancreatitis in which autopsy disclosed a calculus, occluding the duodenal orifice of the ampulla of Vater, but so small that the orifices of the choledochus and pancreatic duct were unobstructed. The two ducts, therefore, were converted into a continuous channel. This made possible the retrojection of bile into the pancreatic duct which probably accounted for the acute pancreatitis present. Stimulated by Opie's observation, other instances of acute pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1936
1936
1966
1966

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…of human hepatic bile (containing 0.5 ml. of duodenal agree with a considerable body of clinical experience (Copeland, 1813;Drysdale, 1861;Battle, 1894;Spencer, 1898;Garrett, 1900;Thompson, 1901;Willard, 1902;Ladd, 1913;Bowers, 1953) although most of the patients reported had suffered from injury to other viscera. Johnston (1961), after reviewing 13 cases of perforation of the common bileduct in infancy, concluded that the prognosis was good.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…of human hepatic bile (containing 0.5 ml. of duodenal agree with a considerable body of clinical experience (Copeland, 1813;Drysdale, 1861;Battle, 1894;Spencer, 1898;Garrett, 1900;Thompson, 1901;Willard, 1902;Ladd, 1913;Bowers, 1953) although most of the patients reported had suffered from injury to other viscera. Johnston (1961), after reviewing 13 cases of perforation of the common bileduct in infancy, concluded that the prognosis was good.…”
Section: Discussionmentioning
confidence: 66%
“…Dzienbowski (1931) presumed that his patient with this condition had pancreatic enzymes in the fluid and noted that these recently had been found in the peritoneal fluid of a patient reported by Siefert (1931). Colp, Gerber, and Doubilet (1936) reported 2 patients with acute sterile non-perforative biliary peritonitis in whom pancreatic enzymes were present in the bile. One patient had free bile-stained fluid in the peritoneal cavity; the other had a loculated layer of bile-stained fluid outside the gall-bladder.…”
Section: Place Of Trypsin In Bilementioning
confidence: 99%